2020
DOI: 10.3390/polym12020279
|View full text |Cite
|
Sign up to set email alerts
|

Particle Image Velocimetry (PIV) Investigation of the Turbulent Airflow in Slot-Die Melt Blowing

Abstract: In order to explore the forming mechanism of the fiber whipping motion in slot-die melt blowing, the turbulent airflow in slot-die melt blowing was measured online with the approach of the Particle Image Velocimetry (PIV) technique. The PIV results visualized the structure of the turbulent airflow and provided the distributions of air velocity components (vx, vy, and vz). Moreover, the PIV results also demonstrated the evolutive process of turbulent airflow at successive time instants. By comparing the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Due to it becoming a popular method due to its application on producing high-efficiency air filters in industry [ 1 , 2 , 3 , 4 ], melt-blowing technology has been of increasing interest in recent years owing to the development of nanotechnology [ 5 , 6 , 7 , 8 , 9 ]. During the melt-blowing process, polymer melts are attenuated into micro/nanofibrous nonwovens with the help of high-speed hot air jets [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to it becoming a popular method due to its application on producing high-efficiency air filters in industry [ 1 , 2 , 3 , 4 ], melt-blowing technology has been of increasing interest in recent years owing to the development of nanotechnology [ 5 , 6 , 7 , 8 , 9 ]. During the melt-blowing process, polymer melts are attenuated into micro/nanofibrous nonwovens with the help of high-speed hot air jets [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A hot-wire anemometer was also applied for measuring the fluctuating velocity and temperature of melt-blown airflow. , The results showed that the temperature fluctuation revealed a regular profile like a sine or cosine curve; however, the velocity fluctuation was irregular. More recently, Xie et al explored the melt-blown air turbulence by particle image velocimetry (PIV); they found that the two ejected air jets from a pair of slots integrated immediately and began to form an S-shaped turbulent structure, and their work revealed the same structure of air turbulence and the specific fiber whipping motion in slot-die melt blowing.…”
Section: Introductionmentioning
confidence: 99%
“…12 Another technique called the particle image velocimetry (PIV) is used to measure the turbulent air flow field in the melt blowing process in an effort to explain the fiber whipping motion. 49 The PIV technique involves emitting numerous tracer particles into the air flow field and then using a pulsed laser beam to detect their trajectory. PIV helps visualize the structure of the turbulent air flow and measure the spatial distribution of the velocity at any time instance.…”
Section: ■ Overviewmentioning
confidence: 99%